Biogas production, upgradation and slurry management - Vijay, V.K. (New Delhi, India : N.K. Mehra for Narosa Publishing, 2012)
Biogas production, upgradation and slurry management covers practical aspects of biogas genertaion, biogas plants, biogas upgradation and its commercial applications, CDM opportunities in biogas, government policies and programmes, biogas slurry handling and manangement etc.
Keywords: Biogas -- India